My Story - Mordaunt, Niall (REACH: Journal of Inclusive Education in Ireland, 1989)
In his own words, the 13 year old writer of this article describes with frankness the bravery of his early years in his struggle with spina bifida, his determination through his primary school years and his hopes for his future. He wrote his story while in 6th class in Ringsend National School, Dublin.